Dynamic magnetization of thermally blocked iron oxide nanoparticles characterized by a sensitive AC magnetometer using a resonant excitation coil - Mohd Mawardi, Saari; Nazatul Shareena, Suhaimi; M. H., Sulaiman; Nurul Akmal, Che Lah; Kenji, Sakai; Toshihiko, Kiwa; Keiji, Tsukada (2018)
In this study, a development of a sensitive AC magnetometer using a resonant Litz wire coil is reported. Using the AC magnetometer, we characterized the dynamic magnetization of thermally blocked iron oxide nanoparticles in different viscosity of carrier liquid. The multi-core iron oxide nanoparticles have a mean core size of 12 nm. The magnetization curve was measured by a specially developed high-Tc SQUID magnetometer. Using the measured dynamic magnetization, we then reconstructed the distribution of the hydrodynamic size of the particles by assuming a log-normal distribution of particle size in a Debye function of magnetic response. The AC susceptibility model by Shliomis and Stepanov which accounts for anisotropic directions of the easy axes of magnetic nanoparticles with respect to the excitation field direction, was used. The reconstructed hydrodynamic sizes agreed with the size determined from dynamic light scattering method. The peak of imaginary component of magnetization shifted to lower frequency region as viscosity increased. We showed that harmonics ratio and the lagging phase can be used to independently determine the viscosity of carrier liquid. A highly sensitive exploration of dynamics properties of magnetic nanoparticles can be expected by using the developed system.